Analisis Pemodelan Dinamik Motor Sinkron Tiga Fasa Pada Percobaan Tegangan Tidak Seimbang - Reynaldo Rizkika Putra; Paulus Setiawan; Bambang Sudibya (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2022)
The problem that often arises lately in electrical motors is the occurrence of voltage imbalances. Unbalanced voltage is an unequal voltage value in a three-phase voltage system contained in an electric power system. On the basis of these problems, it is necessary to conduct research that can analyze the dynamics of the performance of synchronous motors. The frame of reference theory is used to analyze the performance of both synchronous and induction motors. This study implements the modeling of the transformation on the natural axis abc and the transformation on the dq0 axis of the stator and rotor variables in the coordinates of the reference frame. The results of this study indicate that the voltage imbalance from 1% to 5% at the electromagnetic torque has decreased from 8.5 Nm to 6 Nm, the stator current in one phase has increased from 44.2 amperes to 45.2 amperes, the motor rotation speed has decreased from 1820 rpm to 1570 rpm, motor output power decreased from 25550.05 watts to 18968.45 watts, and power efficiency decreased from 98.24% to 82.43%.